Mild and efficient photocatalytic coupled alcohol oxidative dehydrogenation and CO2 reduction driven by visible light. Issue 7 (18th March 2022) - Zhu, Jiekun; Yi, Zheng; Luo, Mingyu; Deng, Youer; She, Jialuo; Liu, Yachun; Zhang, Chao; Yang, Bo; Tang, Senpei; Fu, Zaihui
Abstract : Al 3+ -Doped decatungstate (Al-DT) that in situ -generates the double-reduced blue H2 DT playing a crucial role in achieving the reduction of CO2 can efficiently catalyze the coupled reactions of alcohol oxidative dehydration and CO2 reduction under visible light illumination. Abstract : The advanced coupled conversion technique based on the oxidative dehydrogenation (ODH) of alcohols and the reduction of CO2 is a potential strategy to solve the current energy and environmental crisis, and is of great significance for the upgrading conversion of CO2 to fuels. This work discloses that the Al 3+ species-doped decatungstates (Al-DTs) can efficiently catalyze the coupled conversion of various aliphatic and aromatic primary/secondary alcohols with CO2 in MeCN under visible light illumination and very mild conditions, and the reductive efficiency of CO2 depends on the doping levels of Al 3+ species in Al-DTs and the ODH reactivity of alcohols. After continuously illuminating for 12 h, the best, 4% Al-DT can provide 437 μmol acetophenone as the ODH product and 218 μmol CO2 reduction products (formic acid and methanol) with 1.82 h −1 turnover frequency in the photocatalytic coupled conversion of α-phenylethanol with CO2 . Also, a trace amount of CO is detected from the photocatalytic coupled reactions. UV-vis spectra and isotope tracing tests using heavy oxygen water (H2 18 O) support that the doubly-reduced blue H2 DT species generated from the photocatalytic ODH of alcohols turns into its oxygen-deficient form ([DT 2− ]v ) via an intra-molecular dehydration or lattice oxygen transfer and the latter, with the help of doped Al 3+ species, may efficiently reduce CO2 to fuels via the multi-step proton-coupled electron transfer (PET) pathway.